Social Media Marketing Strategy of Little Quokka Publisher during The Covid-19 Pandemic - Nabilla Anasty Fahzaria (UIN Salatiga, 2022)
Currently, the whole world is facing the Covid-19 pandemic which has affected various lines of business around the world, including the book publishing industry. Book stores closings and restrictions on public space capacity caused publisher revenues to decline by up to 70%. One new publisher from Bandung named Little Quokka Publisher utilizes social media marketing strategy in marketing their children's book products. This article discusses how Little Quokka Publisher carries out a social media marketing strategy by maximizing Instagram content production to increase product sales in difficult times and successfully market their products. This research used a qualitative descriptive research method through interviews with the Little Quokka publisher team to uncover the four principle pillars of social media marketing. The results show that publishers take advantage of marketing book products through social media by paying attention to several unique strategies that are applied in creating content such as humanistic, creative, and relatable. In addition, in digital content marketing, the team tries to get to know products, doing content research, and be social.